Variations in the Microcystin Content of Different Fish Species Collected from a Eutrophic Lake - Mylynda Shaskus; Carl Oesch; John F. Estenik; Justine R. Schmidt; Roman Khidekel; Gregory L. Boyer (Toxins, 2013)
Microcystins produced from cyanobacteria can accumulate in fish tissues. Liquid chromatography coupled with tandem quadrupole mass spectrometry (LC-MS/MS) is an attractive alternative to immunoassays for the determination of low concentrations of microcystins in tissues. Fish taken from Grand Lake St. Marys, a eutrophic lake in Ohio, USA, were analyzed for microcystin-LR in their fillets using LC-MS/MS. Of 129 fish tested for microcystins, only black crappie (Pomoxis nigromaculatus) and common carp (Cyprinus carpio) tested positive for microcystin-LR. Less than 10% of Pomoxis and 7% of Cyprinus samples contained measurable levels of microcystin-LR. Statistical analysis yielded a p-value of 0.07 between Pomoxis and the pooled results of the other four fish species. However, this comparison was complicated by the large difference in sample size between species. Further sampling in Grand Lake St. Marys for microcystin-LR would help determine if microcystin-LR exposure occurs through foodweb transfer.